Territórios e identidades dos ribeirinhos pescadores vazanteiros do rio Araguaia em Araguatins, Tocantins - Eliseu Pereira de Brito; Matheus Miranda Shimasaki (Confins)
In the text, it is proposed to analyze the territory of the ribeirinhos, vazanteiros fishermen of the Araguaia river in the municipality of Araguatins, north of the state of Tocantins. During research, it was identified that the ribeirinhos build their territories much more by identification, study of their interdependencies with the Araguaia River, than by possession of the territory. To do this, the territory was analyzed in the light of what Jöel Bonnemaison (1987) proposes, that is to say as a network of places and routes that the subjects have built on the ground, a symbolic territory. Territorial identity was treated according to the three pillars: myth, history and territory and according to the identities of persistence proposed by Brito (2016). The research method consisted of conducting interviews with the ribeirinhos, vazanteiros fishermen, seeking to understand the construction of their territories and their identities, and guided by the tools proposed in the Participatory Rural Diagnosis - DRP in Verdejo (2006). Descriptive research was also used with landscape observation and the use of DRP to collect, organize and analyze field information. It has been found that the territories of the ribeirinhos, vazanteiros fishermen, are built by means of a set of fishing, housing and recreation places and by routes built on the Araguaia river, a heritage of their ancestors. These are subjects who have built an interdependence with the river and who perceive it as necessary to maintain their territories. Even with the evolutions and the introduction of new techniques in fishing and in the way of working of ribeirinhos, there is knowledge which is perpetuated and which allows them to keep their identity, an identity forged by the persistence on the territory.